A Co-Citation and Co-Word Analysis of Islamic Accounting and Accounting Research - Priyono, Priyono Puji Prasetyo; Khusnul Hidayah; Wahyudi, Rina Tushofiah; Wahyudi, Andika Prasetia; Wahyudi, Vrisas Meri Setiawan; Wahyudi, Dimas Arya Pramono (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2024)
Introduction: The study of conventional accounting has been a cornerstone in both academic research and practical business applications for many years. It provides a comprehensive framework for financial reporting, decision-making, and regulatory compliance, which is universally recognized and applied across various industries globally. This widespread adoption is attributed to its well-established principles, which have been refined and tested over time, making it a reliable foundation for managing financial affairs. Purpose: This article aims to provide the intellectual structure and evolution of Islamic Accounting and Accounting Research themes. Methodology: The authors utilized co-citation and co-word analysis to select 413 Islamic Accounting and Accounting from the Scopus database. The timeframe of the research encompasses articles published from 2010 through January 2024. Findings: The research findings can be concluded, firstly, countries that have a great interest in Islamic Accounting and Accounting include Malaysia, Indonesia, and the United Kingdom. New themes for future research directions by means of co-citation and joint word analysis are suggested. Prospects in Islamic accounting and accounting include 'technology and automation', 'big data', and 'regulatory reform', and 'nuclear fuel accounting'.